A study on factors influencing job satisfaction among employees in Asia Roofing Industries Sdn Bhd, Bukit Kemuning / Sarrah Sharrina Abdul Karim - Abdul Karim, Sarrah Sharrina (2009)
Project paper titled “A Study on Factors Influencing Job Satisfaction among Employees in Asia Roofing Industries SDN BHD, Bukit Kemuning” is conducted as partial requirement to fulfill the requirement as needed by the faculty of Business Management, MARA University of Technology (UiTM). The purpose of this study is to identify the most factors that influence job satisfaction among employees in the Asia Roofing Industries, their level of job satisfaction, and the significant relationship between factors influencing their job satisfaction. Analysis of the data about the level of job satisfaction showed that on average employees in Asia Roofing Industries Sdn Bhd, Bukit Kemuning was not satisfied with their relationship with the top management. However, on the other hand, they were very satisfied with their relationship with the colleagues. Besides, further analysis revealed that the relationship with the colleagues is the most factors that influence job satisfactions among employees in Asia Roofing Industries. In addition, by using the Pearson correlation method, analysis of 80 respondents revealed that there was a significant and positive relationship between promotion and recognition, relationship with colleagues, and working environment, except for salary and relationship with supervision, where indicates a weak significant relationship because the correlation coefficients only at 0.135 and 0.123 respectively which is near to 0.